Government and Change in Lesotho, 1800–1966 - Machobane, L B. author. aut Link
XIX, 374 p.
Keywords: This study of political institutions provides an objective appraisal of the precolonial institutions of the Basotho before colonial rule in 1868. It appraizes the impact of colonial rule on the old political structure, the introduction of new institutions and the development of new perceptions.